Firm entry deregulation, competition and returns to education and skill - Ferreira, Priscila (2013)
This paper studies the effect of firm entry deregulation on the returns to skill and education. We use matched employer-employee data for the universe of workers and firms in Portugal and exploit a comprehensive episode of entry deregulation, unique in the industrialized world, as a quasi-natural experiment to investigate how increased competition affects wages. We find that after the reform the returns to a university degree increased by around 5 percent and the returns to skills increased by around 3 percent. We include match (worker-firm) fixed effects and thus identify the effect from individuals who stay in the same firm after the reform. Results are therefore not driven by changes in employment composition, and are supportive of education and skill becoming more valuable after the reform.